Кон Knut H. Sørensen and James Stewart (Eds.), Digital Divide and Inclusion Measures: A Review of Literature and Statistical Trends on Gender and ICT: Për Knut H. Sørensen and James Stewart (Eds.), Digital Divide and Inclusion Measures: A Review of Literature and Statistical Trends on Gender and ICT - Ivanovska, Marija; Ahmeti, Lindita (Identities: Journal for Politics, Gender and Culture, 2004)
Author(s): Marija Ivanovska | Марија Ивановска Title (Macedonian): Кон Knut H. Sørensen and James Stewart (Eds.), Digital Divide and Inclusion Measures: A Review of Literature and Statistical Trends on Gender and ICT Title (Albanian): Për Knut H. Sørensen and James Stewart (Eds.), Digital Divide and Inclusion Measures: A Review of Literature and Statistical Trends on Gender and ICT Translated by (Macedonian to Albanian): Lindita Ahmeti Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 3, No. 1 (Summer 2004) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 241-243 Page Count: 3 Citation (Macedonian): Марија Ивановска, „Кон Knut H. Sørensen and James Stewart (Eds.), Digital Divide and Inclusion Measures: A Review of Literature and Statistical Trends on Gender and ICT“, Идентитети: списание за политика, род и култура, т. 3, бр. 1 (лето 2004): 241-243. Citation (Albanian): Marija Ivanovska, „Për Knut H. Sørensen and James Stewart (Eds.), Digital Divide and Inclusion Measures: A Review of Literature and Statistical Trends on Gender and ICT“, përkthim nga Maqedonishtja Lindita Ahmeti, Identities: Journal for Politics, Gender and Culture, Vol. 3, No. 1 (Summer 2004): 241-243.